Intravital Microscopy for the Study of Hepatic Glucose Uptake. Issue 5 (25th May 2021) - Stefkovich, Megan L.; Kang, Sun Woo Sophie; Porat‐Shliom, Natalie
Abstract: The liver is central in maintaining glucose homeostasis. Indeed, impaired hepatic glucose uptake has been implicated in the development of hyperglycemia in type II diabetes (T2D) and non‐alcoholic fatty liver disease (NAFLD). However, current approaches to evaluate glucose mobilization rely on indirect measurements that do not provide spatial and temporal information. Here, we describe confocal‐based intravital microscopy (IVM) of the liver that allows the identification of hepatocyte spatial organization and glucose transport. Specifically, we describe a method to fluorescently label hepatic landmarks to identify different compartments within the liver. In addition, we outline an in vivo fluorescent glucose uptake assay to quantitatively measure glucose mobilization in space and time. These protocols allow direct investigation of hepatic glycemic control and can be further applied to murine models of liver disease. © Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Mouse surgical procedure and positioning for liver intravital imaging Basic Protocol 2 : Fluorescent labeling and intravital imaging of mouse hepatic compartments Basic Protocol 3 : Mouse hepatic glucose uptake assay and intravital imaging analysis